2020
DOI: 10.1177/0885066620954364
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Barotrauma in Patients With COVID-19 Pneumonia During Prolonged Invasive Mechanical Ventilation – A Case-Control Study

Abstract: Background: SARS-CoV2 can cause pulmonary failure requiring prolonged invasive mechanical ventilation (MV). Lung protective ventilation strategies are recommended in order to minimize ventilator induced lung injury. Whether patients with COVID-19 have the same risk for complications including barotrauma is still unknown. Therefore, we investigated barotrauma in patients with COVID-19 pneumonia requiring prolonged MV. Methods: All patients meeting diagnosis criteria for ARDS according to the Berlin Definition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 11 publications
(18 reference statements)
2
84
2
1
Order By: Relevance
“…We report five patients with pneumomediastinum of 92 critically ill, mechanically ventilated adults with ARDS from COVID-19 at our institution from March 1, 2020, through August 31, 2020 ( Figure 1 ). Unlike other reports ( 4 , 5 ), no patient had pneumothorax or required tube thoracostomy at diagnosis, suggesting alveolar rupture occurred without disruption of visceral pleura. Pneumomediastinum developed between 24 hours before and 9 days after initiation of mechanical ventilation without evidence of tracheal injury or the use of recruitment maneuvers.…”
contrasting
confidence: 69%
“…We report five patients with pneumomediastinum of 92 critically ill, mechanically ventilated adults with ARDS from COVID-19 at our institution from March 1, 2020, through August 31, 2020 ( Figure 1 ). Unlike other reports ( 4 , 5 ), no patient had pneumothorax or required tube thoracostomy at diagnosis, suggesting alveolar rupture occurred without disruption of visceral pleura. Pneumomediastinum developed between 24 hours before and 9 days after initiation of mechanical ventilation without evidence of tracheal injury or the use of recruitment maneuvers.…”
contrasting
confidence: 69%
“…Additionally, a case-report by Udi et al reported 8 patients (40%) developed severe barotrauma during mechanical ventilation. Of the 8 patients, one had tension pneumothorax and four had pneumothorax not causing hemodynamic compromise [ 19 ]. All patients received chest tubes.…”
Section: Discussionmentioning
confidence: 99%
“…Other common chest complications of COVID-19 pneumonia include PNX, PM, pneumopericardium, and subcutaneous emphysema, which are usually secondary to pulmonary barotrauma from mechanical ventilation in the ICU ( Figure 13 ) [ 184 ]. They are usually associated with a long hospital stay and higher mortality and occurred in 15 to 40% of COVID-19 patients who underwent mechanical ventilation [ 185 , 186 ]. Mechanical ventilation with high positive end-expiratory pressure (PEEP) can increase high intra-alveolar pressure, causing alveolar rupture through the disproportionate distribution of volume and pressure from the ventilator with air dissection along the bronchovascular sheets toward the mediastinum, leading to PM.…”
Section: Covid-19 Complicationsmentioning
confidence: 99%
“…Occasionally, air in the mediastinum can escape into the pleural space and cause pneumothorax (PNX), or through the parietal pericardium and cause pneumopericardium. Air can also travel toward the thoracic inlet and into neck soft tissue, causing subcutaneous cervical-facial emphysema, and into the peritoneal spaces of the abdomen, causing pneumo-retroperitoneum [ 185 , 186 , 187 ]. Gattinoni et al [ 178 ] found that in critically ill COVID-19 patients, the incidence of PNX increased in those who were mechanically ventilated for a long period of time.…”
Section: Covid-19 Complicationsmentioning
confidence: 99%
See 1 more Smart Citation